A REVIEW ON MICRO-GRID AND DEMAND SIDE MANAGEMENT AND THEIR RELATED STANDARDS - Md Nor, Nor Hafizah; Sapar, Ahmad Farid; Ramani, Anis Niza; Shamshiri, Meysam; Gan, Chin Kim (2013)
Nowadays, the standards of industrial civilization are known as a reliable solution and consequently, comprehensive standards for power system has been developed for use in national and international networks. Malaysia’s efforts to develop power system utilization standards are still ongoing and maturing. However, in some cases it is observed that the standards are not be considered in the power system. In the results, besides reducing productivity, quality, and losing, risks and hazards are realized residents, staff, equipment and electrical installations and facilities. This paper discusses the consideration of the standards of the Micro-Grids (MGs), Islanding and Demand Side Management (DMS) that can be applied in the power system network. Aspects and standards of each role in the power system network are described in the following subsection.